Some Biological Aspects of Bloodworm: Chironomus pallidinubeculosus Tokunaga, 1964 (Diptera: Chironomidae) - Patipat Tevapawat; Nisarat Tungpairojwong (Tropical Life Sciences Research, 2024)
Some biological aspects of local bloodworms in Thailand were investigated. In this study, the larvae of one species of bloodworm, identified as Chironomus pallidinubeculosus Tokunaga 1936, were reared in plastic containers at 25°C and fed with fish feed solutions three days per week. The eggs sample were processed by histological and TEM techniques. Yield (g/m2), moisture, ash, crude protein, crude lipid, crude fibre and gross energy (KJ/g) were determined in reared larvae. The results showed that C. pallidinubeculosus larvae could survive and be bred in plastic containers, controlled laboratory conditions, and have four instars. The suitable physico-chemical parameters during rearing were low to moderate dissolved oxygen (1.18 mg/L–5.00 mg/L), electrical conductivity (462 ?S–714 ?S), and total dissolved solids (249 mg/L–378 mg/L). Moreover, adults had a high average number of eggs per one egg mass from 193.2 ± 49.99 to 331.86 ± 80.23 and an average hatchability of 90.69% to 94.49% during the 1st to 3rd generations, respectively. The life cycle of this study was approximately 19 to 23 days. Polylecithal and centrolecithal eggs were observed. After gelatinous mass removal, the egg was covered by non-regularly exochorionic jelly. The internal morphology of the egg is mainly composed of proteid yolk, lipids and dense granular. Larvae constituted 89.78% water; they had a high 15th day yield (g/m2), and the minimum area of larvae for mass culture was 1.2 cm2. The proximate composition analysis in reared larvae showed that crude protein, crude lipid crude fibre and gross energy were higher than its feed. The biology aspect study of the bloodworms found they were easy to culture; they should be considered a model organism for further ecology, nutrition and toxicology studies.